2022
DOI: 10.3390/ijms23020592
|View full text |Cite
|
Sign up to set email alerts
|

DM1 Transgenic Mice Exhibit Abnormal Neurotransmitter Homeostasis and Synaptic Plasticity in Association with RNA Foci and Mis-Splicing in the Hippocampus

Abstract: Myotonic dystrophy type 1 (DM1) is a severe neuromuscular disease mediated by a toxic gain of function of mutant RNAs. The neuropsychological manifestations affect multiple domains of cognition and behavior, but their etiology remains elusive. Transgenic DMSXL mice carry the DM1 mutation, show behavioral abnormalities, and express low levels of GLT1, a critical regulator of glutamate concentration in the synaptic cleft. However, the impact of glutamate homeostasis on neurotransmission in DM1 remains unknown. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…We propose that impaired astrocyte arborization and polarity in DMSXL mice (comparable to that found in other mouse models of astrocyte dysfunction 24 , 68 ), may affect the ultrastructure and maturation of the synapse in vivo, in terms of astroglial coverage, synapse-to-astrocyte distance, and dendritic arborization. In this context, it will be important to investigate defects in the ultrastructural and functional interplay between astrocytes and neurons, which may contribute to the aberrant tonic currents and synaptic plasticity of DMSXL mice 69 .…”
Section: Discussionmentioning
confidence: 99%
“…We propose that impaired astrocyte arborization and polarity in DMSXL mice (comparable to that found in other mouse models of astrocyte dysfunction 24 , 68 ), may affect the ultrastructure and maturation of the synapse in vivo, in terms of astroglial coverage, synapse-to-astrocyte distance, and dendritic arborization. In this context, it will be important to investigate defects in the ultrastructural and functional interplay between astrocytes and neurons, which may contribute to the aberrant tonic currents and synaptic plasticity of DMSXL mice 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that DMSXL mice have elevated extracellular GABA levels and tonic currents in the hippocampus. This dysfunction coincided with RNA foci accumulation in areas of the hippocampus and by the mis-splicing of candidate genes with relevant functions in neurotransmission, one of which being Gabrg2 ( Potier et al, 2022 ). These results further support our behavioral findings of increased GABA sensitivity in Mbnl2 KO mice.…”
Section: Discussionmentioning
confidence: 98%
“…This process creates neuronal circuits that facilitate communication between neurons through chemical synapses. Abnormal neurotransmitter levels reflect dysregulation of brain functions that manifest as physical, psychologic, and neurodegenerative diseases [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Neurotransmittersmentioning
confidence: 99%